Hierarchically Structured Zeolites: Nature‐Inspired, Computer‐Assisted Optimization of Hierarchically Structured Zeolites (Adv. Mater. Interfaces 4/2021). Issue 4 (19th February 2021) - Coppens, Marc‐Olivier; Weissenberger, Tobias; Zhang, Qunfeng; Ye, Guanghua
Abstract : Introducing broad pores could decrease diffusion limitations in zeolite catalysis – but what is the optimal structure? In article number 2001409 by Marc‐Olivier Coppens, Guanghua Ye, and co‐workers, a systematic, optimal design methodology is discussed. It borrows lessons from nature to guide hierarchically structured zeolite synthesis, aided by multiscale modelling. Design rules of thumb are derived and illustrated. Controlling surface barriers is a new challenge, with more scope for inspiration from nature.